(3GdQO Ydi GdRfGObI hGdLgejIs - (3CMeO Hf eMeO Hf MfHd, CHh YHO Gddg, GdTjHGfqj GdhGFdj,J (B241 (3g` s
(3ChdgG (B:s
(3CNHQfG GHh WGgQ GdeHGQc bGd CfHCfG YHO Gddg Hf CMeO Hf MfHd QMeg Gddg bGd gPG eG GNQLg Edi QMeI Gddg ai GdQO Ydi GdRfGO hGdLgejI aejG TcJ ajg ef eJTGHg GdbQGf s
(3BNQgG (B:s
(3hQLY Yf Gdbhd GdPi jNGda GdcJGH hGdSfI hbGd jbhd GdYdeGA hgh bhd GdegGLQjf hGdGfUGQ hJQc Ojf Lge hTjYJg BNQ GdcJGH s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B203 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B96s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3GdJhMjO hGdedd hGdfMds